Paralytic sciatica revealing a thigh hematoma: a case report - Hassnaoui, Youssef El; Mohamed, Tazi; Ansari, Abdelaziz El; Madani, Hamza; Boulazaib, Issam; Hicham, Ait Benali; Mohammed, Shimi (International Journal of Research in Orthopaedics, 2025)
Authors report the case of a 27-year-old man, on fondaparinux for prophylaxis, who presented to the emergency department with acute, paralyzing, painful sciatica of the left lower limb, following minor trauma. Clinical examination, combined with angio-computed tomography (angio-CT), revealed a voluminous compressive hematoma in the posterior compartment of the thigh, probably of muscular origin. The patient underwent emergency surgical evacuation, during which approximately one liter of hematoma was removed. The postoperative course was favorable, and appropriate rehabilitation led to full neurological recovery within 12 months. This case highlights the importance of considering a compressive hematoma in the differential diagnosis of sciatic paralysis following trauma, however minimal, particularly in patients on anticoagulants. It also highlights the crucial role of early diagnosis and multidisciplinary management.